SEG Technical Program Expanded Abstracts 2005 2005
DOI: 10.1190/1.2147858
|View full text |Cite
|
Sign up to set email alerts
|

Unique near‐surface seismic‐reflection characteristics within an abandoned salt‐mine well field, Hutchinson, Kansas

Abstract: High-resolution seismic reflections have been used effectively to investigate sinkholes resulting from the dissolution of a bedded salt unit found throughout most of central Kansas. A seismic reflection survey was conducted to investigate the shallow subsurface between a sinkhole that formed catastrophically within a few tens of meters of a main east/west rail line. Data quality was significantly below expectations and not equivalent to other seismic data from this area where acquisition parameters, equipment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Resolution and signal-to-noise ratio of near-surface seismic reflection data are appreciably improved through optimized source coupling (Walters et al, 2006), use of low-noise baseplate and mass sensors and non-telemetry pilot (Rademacker et al, 2005), site-specific pre-correlation processing approaches (Miller et al, 2005), and site-and equipment-specific approaches to the correlation step (correlation with synthetic or deconvolution with ground force). Unlike an explosive or projectile source where saturated, fine grain sediments provide the best transmission of high frequency signal (Miller et al, 1986), the highest frequency response was observed when the baseplate was coupled to a compacted, minimally deforming surface.…”
Section: Introductionmentioning
confidence: 99%
“…Resolution and signal-to-noise ratio of near-surface seismic reflection data are appreciably improved through optimized source coupling (Walters et al, 2006), use of low-noise baseplate and mass sensors and non-telemetry pilot (Rademacker et al, 2005), site-specific pre-correlation processing approaches (Miller et al, 2005), and site-and equipment-specific approaches to the correlation step (correlation with synthetic or deconvolution with ground force). Unlike an explosive or projectile source where saturated, fine grain sediments provide the best transmission of high frequency signal (Miller et al, 1986), the highest frequency response was observed when the baseplate was coupled to a compacted, minimally deforming surface.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the ability of seismic-reflection methods to image the subsurface expression of sinkholes and bedding geometries within the disturbed zone using compressional waves (Miller et al, 1993;Miller et al, 2005); however, no work has been done to evaluate void-induced changes in the localized stress field or the effect on seismic properties that may be indicative of near-term roof failure potential.…”
Section: Introductionmentioning
confidence: 99%